Detention of Kloop media staff intensifies crackdown on independent journalism (Amnesty International, 2025)
Detaining journalists for their work, denying access to legal counsel and carrying out warrantless searches of homes violates both Kyrgyzstan’s own legal obligations and international human rights standards
Kyrgyzstan